PSIKOLOGI KOMUNIKASI UNTUK MEMAKSIMALKAN INTERNALISASI NILAI-NILAI TOLERANSI PADA ANAK USIA DINI - Drajati Ekaningtyas, Ni Luh (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Conflicts and acts of violence due to intolerance in Indonesia are still quite high, both in the social and educational environment. Intolerance is suspected to occur due to childhood habits, therefore internalization of tolerance values from an early age blaze as one solution that can be done to overcome this problem of intolerance. Internalization of tolerance values from an early age is expected to be able to form tolerant individuals so that the level of conflict and violence that occurs due to intolerance will decrease. One of the things that parents and teachers can do to maximize the internalization of tolerance values in early childhood is to apply the psychology of communication in the process of internalization. The application of communication psychology will help early childhood achieve : (1) understanding, (2) pleasure, (3) change in attitude, (4) good social relations, and (5) actions related to tolerance values.Â